Using Lean Six Sigma to Improve Insurance Claims Processes in Emerging Markets - Mwaura, Frida (2019)
The marriage of Lean and Six Sigma as approaches to quality management has yielded empirical evidence of significant improvement in organisations in a variety of sectors and regions. While both Lean and Six Sigma have their roots in manufacturing, their use has since been extended to services, including insurance, particularly since the early 2000s. However, there is very limited academic and industry information on the implementation of Lean Six Sigma in emerging markets particularly in Africa. A desktop study of insurance claims processes in India and Kenya revealed significant waste that could be eliminated or minimized through the implementation of Lean Six Sigma. The study proposed process changes that if implemented could improve service delivery by insurance companies in India and Kenya.